Digitalization of Operations Management with Emotional and Intelligence Tools. Blockchain and IoT integration, the last disruption? - Silvia Serrano-Calle; Tomás Robles; Diego Martín; Raquel Mateos (International Telecommunications Society (ITS), 2018)
Digital advances and the emergence of disruptive technologies have dramatically changed the business models across sectors and operations economics. The scope of this paper is to contribute to analyze the current disruptive revolution in operations management in a digitalized global market focusing on the impact of blockchain technology and IoT integration. New intelligence tools and emotional analysis are contributing to add trust and promote digital expansion across different sectors. Given the high economic impact of the operations management on virtually all productive enterprises, the benefits of digitalizing operations have continuously increased productivity and enhanced international competitiveness. This paper studies the opportunities of what could be one of the last disruptions in operations management, the introduction of blockchain combined with IoT technology and emotional intelligence tools to automate, in a cryptographically verifiable process, activities in digital supply chain networks. Keywords: Blockchain, IoT, Supply Chain Network, Operations Management, Digital Policy Funding: The research leading to these results has received funding from the Spanish Ministry of Economy and Competitiveness through SEMOLA project (TEC2015-68284-R) and from the Autonomous Region of Madrid through MOSI-AGIL-CM project (grant P2013/ICE-3019, cofunded by EU Structural Funds FSE and FEDER).
Keywords: L23; L81; M11; 330